LANGIT DALAM PANDANGAN MANUSIA: ANALISIS LINTAS BUDAYA TENTANG SISTEM KOSMOLOGI, NARASI MITOLOGIS, DAN PRAKTIK SPIRITUALITAS - Agustina Rahayu Sianturi; Dhea Zuhrika; Angelo Arevallo Simanullang; Ramadhan Fitriani; Elsa Kardiana (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This research explores the diversity of celestial views and their relationship with spirituality practices in different cultures around the world. Cosmology, as an understanding of the origin and structure of the universe, as well as mythologies that explain natural phenomena, are the main focus of this analysis. Using a descriptive qualitative approach through a systematic literature study, the research covers five to seven representative cultures from the continents of Asia, Europe, the Americas, Africa and Oceania. The results show that each culture has a unique way of understanding and interpreting celestial phenomena, reflecting not only astronomical knowledge but also inherited values, beliefs and traditions. Moreover, the relationship between the view of the sky and the practice of spirituality across different cultures shows that the sky serves as a source of inspiration, knowledge and spirituality. The research also highlights the importance of historical documentation in understanding human interactions with their environment, as well as how sky views shape cosmological systems and mythological narratives. The findings provide deeper insights into cultural diversity and encourage constructive dialogue between different communities, as well as reduce conflict due to cultural misunderstandings.